Integrating datasets from herbarium specimens and images to treat a Neotropical myrtle species complex - Gaem, Paulo Henrique; Andrella, Giovani Carlos; Maurin, Olivier; Bittrich, Volker; Mazine, Fiorella Fernanda; Lucas, Eve; Estanislau do Amaral, Maria do Carmo (Annals of botany, 2025)
Herbaria are the most important source of information for plant taxonomic work. Resources and technologies available today, such as digitized collections and herbarium DNA sequencing, can help accelerate taxonomic decisions in challenging plant groups. Here we employ an integrative methodology relying exclusively on herbarium specimens to investigate species boundaries in the Neotropical Myrcia neoobscura complex (Myrtaceae). We collected morphometric data from high-resolution images of herbarium sheets and analysed them using hierarchical clustering. We posteriorly tested the obtained morpho-groups with phylogenomics using the Angiosperms353 probe kit. We also gathered phenological and geographical information from specimen labels and built phenological histograms and ecological niche models to investigate ecological differences amongst taxa. Current circumscriptions of Myrcia arenaria, Myrcia neoglabra and Myrcia neoregeliana are confirmed in this study. Conversely, the four pieces of evidence together support Calyptranthes langsdorffii var. grandiflora, Marlierea regeliana var. parviflora and Marlierea warmingiana as separate from Myrcia marliereana, Myrcia neoriedeliana and Myrcia neoobscura, respectively, contrary to arrangements proposed by previous authors. Integrated analyses also support separation between Myrcia excoriata and two similar, undescribed taxa. Our data reveal the need for major changes in the systematics of the group, with recognition of 12 species. The successful delivery of our study aims was possible due to obtaining robust, high-quality data from museum specimens. We emphasize the importance of maintaining botanical collections physically and digitally available for taxonomic work and advocate their use to accelerate taxonomic solutions of tropical species complexes hollistically. This is urgent, given the paucity of funds for fieldwork and unprecedented rates of habitat loss in the tropics.